Probiotic Potential of Lactic Acid Bacteria Strains Isolated from Artisanal Cheeses: Impact on Listeria monocytogenes Infection - Carla Burgos; Constanza Melian; Lucía M. Mendoza; Susana Salva; Patricia Castellano (Fermentation)
Listeriosis is a disease associated with the consumption of food contaminated with Listeria monocytogenes. Probiotic lactic acid bacteria (LAB) or their postbiotics have been of interest for their anti-listerial effect. This study focused on isolating LAB from artisanal cheeses and characterizing their potential as probiotics. Twelve LAB isolates exhibiting typical LAB traits were evaluated for their ability to survive in simulated gastric juice, hydrolyze bile salts, auto-aggregate, hydrophobicity, and antagonistic activity against L. monocytogenes. The four most promising LAB strains demonstrated anti-listerial probiotic potential and were identified as Latilactobacillus (Lat.) curvatus SC076 and Lactiplantibacillus (Lact.) paraplantarum SC291, SC093, and SC425. The antimicrobial activity of these strains was mainly attributed to bacteriocin-like substances and organic acids. While three Lact. paraplantarum strains were resistant to ampicillin, Lat. curvatus was sensitive to all tested antibiotics. All selected strains exhibited no hemolytic, gelatinase, and lecithinase activity. Exposure to LAB supernatants resulted in a significant reduction in the adhesion and intracellular count of L. monocytogenes in Caco-2 cells, with Lat. curvatus SC076 showing the most significant effect. Based on its probiotic characteristics, Lat. curvatus SC076 is a promising candidate for functional foods, pending further in vivo studies to assess its potential in the food industry.